SULT1A1, CYP2C19 and disease-free survival in early breast cancer patients receiving tamoxifen. (November 2011) - Moyer, Ann M; Suman, Vera J; Weinshilboum, Richard M; Avula, Rajeswari; Black, John L; Safgren, Stephanie L; Kuffel, Mary J; Ames, Matthew M; Ingle, James N; Goetz, Matthew P
Aim: Tamoxifen biotransformation to endoxifen, a potent antiestrogen, is catalyzed by CYP2D6. In addition, CYP2C19 and SULT1A1 have also been implicated in the metabolism of tamoxifen. We sought to evaluate the importance of SULT1A1 copy number and CYP2C19*17 on disease-free survival (DFS) in postmenopausal women randomized to tamoxifen monotherapy in North Central Cancer Treatment Group 89-30-52 from January 1991 to April 1995.Materials & methods: We extracted DNA from paraffin-embedded tumors and determined tumor SULT1A1 copy number and CYP2C19*17 genotype. The association of genotype with DFS was determined using the log-rank test. Multivariate cox modeling was performed using traditional prognostic factors, as well as CYP2D6 genotype. SULT1A1 copy number and CYP2C19*17 genotype was determined in 190 out of 256 patients (95% Caucasian).Results: The median follow-up for living patients was 14 years. DFS did not differ according to SULT1A1 copy number (p = 0.482) or CYP2C19*17 genotype (p = 0.667). Neither SULT1A1 copy number or CYP2C19*17 genotype was associated with disease recurrence in this cohort.Conclusion: Future studies are needed to identify whether other genetic and environmental factors which affect tamoxifen metabolism are associated with tamoxifen clinical outcomes. Original submitted 11 April 2011; Revision submitted 8 July 2011